EVALUASI PENERAPAN PEMBELAJARAN BERDIFERENSIASI PADA SISWA SEKOLAH DASAR - Gloria Yohana Kristuti; Stefanus Christian Relmasira (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to evaluate the implementation of differentiated learning in Natural and Social Sciences (IPAS) subjects in grade IV of SD Kanisius Cungkup and SD Kanisius Gendongan, Salatiga. The research used a mixed methods approach with the CIPP (Context, Input, Process, Product) evaluation model. Data were collected through observation, interviews, and questionnaires, then analyzed using MAXQDA and testing the validity and reliability of the instrument. The results showed that the implementation of differentiated learning had a positive impact on increasing student participation, motivation, and learning outcomes. Evaluation from the aspects of Context (96%), Input (96.93%), Process (96.4%), and Product (98.8%) showed very high category. In addition, the results of qualitative analysis showed a strong link between fun learning activities and students'understanding of the IPAS concept. However, challenges such as time constraints and teacher training needs are still obstacles in its implementation. This study concludes that differentiated learning is effective in creating an adaptive, inclusive and meaningful learning environment. Recommendations are aimed at developing teacher training and long-term planning to optimize the quality of implementation.